The Satisfaction Level Of Postgraduate Students With Services Of Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar - Sudarsana, I Ketut; Luwih, I Made (Jayapangus Press, 2022)
Student satisfaction with the services provided by universities is one of the determining factors for success in achieving the vision and mission of the university. The quality of university services to students is seen as one of the tools to achieve a competitive advantage. Universities must take anticipatory steps in facing increasingly competitive competition and are responsible for exploring and improving all aspects of the services offered by universities. This study aimed to analyze the satisfaction level of postgraduate students with the services of Universitas Hindu Negeri (UHN) I Gusti Bagus Sugriwa Denpasar. This study was survey research. The subject was an active postgraduate student at UHN I Gusti Bagus Sugriwa Denpasar in the even semester of the 2021/2022 academic year. The research results showed that the total of instruments in each field number of respondents in each field, namely 1140 respondents was in governance, management, and cooperation. Furthermore, 570 respondents were in the student affairs field, and 1482 were in the finance and infrastructure field. Last, 5130 respondents were in the education field, and the total number of respondents in each field was 8322 respondents from 144 correspondences. Furthermore, the researchers converted the overall results of the respondents in percentages with a total of 41.85% very satisfied, 53.83% satisfied, 3.50% doubtful, 0.70% dissatisfied, and 0.12 very dissatisfied. Overall, the total instrument results of the satisfaction level of postgraduate students with the services of the UHN I Gusti Bagus Sugriwa Denpasar were in the very high category. In terms of service, they have produced a very satisfactory level of satisfaction. The analysis of the Hindu religious education concept on the postgraduate student satisfaction was studied based on the implementation of activities and routines in daily life based on the Sarasamuccaya scripture. It explains the relationship between the concepts of leadership and decency, Geguritan Niti Raja Sasana, Dharma Sevanam, and Bhagawad Gita as well as the teachings of Dharma Sabda and Panca Satya. It was outlined in the governance, management, and cooperation, the field of student affairs, finance, and infrastructure, and education of a postgraduate student at UHN I Gusti Bagus Sugriwa Denpasar.